Microwave-induced zinc chloride activated palm kernel shell for dye removal - Muhammad Abbas Ahmad Zaini; Tan, Wee Meng; Mohd. Johari Kamaruddin; Siti Hamidah Mohd Setapar; Mohd. Azizi Che Yunus (Universiti Kebangsaan Malaysia, 2014)
This work is aimed to determine the characteristics of activated carbons derived from palm kernel shell (PKS) by microwave-induced zinc chloride activation for dye removal. Activation was performed in a microwave oven at power intensity of 70% for 10 min. The same procedures were repeated for activation using recycled ZnCl2 solution from the first activation. The activated carbons were characterized according to surface area, morphology, functional groups and batch adsorption. The yield for the first activation was 70.7% with surface area of 858m2/g. It was found that the activated carbon prepared using the recycled ZnCl2 still possesses good surface area for methylene blue removal. The adsorption behaviour of the continuous system was well fitted to and could be satisfactorily described by the Yoon and Nelson model.